Liquidity Premium in the Eye of the Beholder: An Analysis of the Clientele Effect in the Corporate Bond Market - Chen, Xuanjuan; Huang, Jing-Zhi; Sun, Zhenzhen; Yao, Tong; Yu, Tong (Management Science, 2020)
This paper examines how liquidity and investors’ heterogeneous liquidity preferences interact to affect asset pricing. Using data on insurers’ corporate bond holdings, we find that illiquidity of corporate bond portfolios varies widely and persistently across insurers and is related to insurers’ investment horizon and funding constraint, consistent with the notion of liquidity clientele. We further find that liquidity clientele affects corporate bond prices—specifically, liquidity premia are lower among corporate bonds heavily held by investors with weaker preference for liquidity. This paper was accepted by Neng Wang, finance.